Thismia kinabaluensis (Thismiaceae), a new species from Mt. Kinabalu, Sabah, Borneo - Nishioka, Tatsuki; Suetsugu, Kenji; Repin, Rimi; Kitayama, Kanehiro (Phytotaxa, 2018)
A new species of Thismia (Thismiaceae), T. kinabaluensis, is described from Mt. Kinabalu, Sabah, Borneo. Thismia kinabaluensis is clearly placed in section Thismia subsect. Odoardoa, in having its creeping vermiform roots and free and equal perianth lobes, and it is distinguished from the other members of this subsection by three anther appendages (one filiform appendage between two club shaped ones) and a pale-blue perianth tube with transverse bars inside. A key to the Malaysian Thismia is provided for easy identification of these mycoheterotrophic plants.